Cell to cell signaling via exosomes (transport of genetic material between cells via exosomes) - Identification of RNA-binding proteins in exosomes capable of interacting with different types of RNA: RBP-facilitated transport of RNAs into exosomes - Valadi, Hadi (University of Gothenburg, 2020)
In the human body, communication between cells takes place in several different ways. Exosomes are a type of extracellular vesicles (30-200 nm in diameter) that also participate in this process. Exosomes can be released from most cell types in the body and exist naturally in different body fluids, such as blood.

In 2007, we showed for the first time that exosomes also transport RNA molecules (both coding and non-coding RNA molecules) between cells (Valadi H. et al. Nature Cell Biology. 2007). The findings describe a new type of 'cell-cell' communication by which different cells send genetic messages to each other by secreting vesicles (exosomes) containing specific RNA molecules.

Our current studies aim to (a) identify cellular actors involved in translocation (packaging) of RNA into exosomes during their biosynthesis, (b) identify the mechanism by which exosomes are taken up by recipient cells/ tissues, and (c) ) discover a method to introduce exogenous/ therapeutic RNA into exosomes, to be used for in vivo transport of therapeutic RNA to different organs.

RNA-binding proteins (RBPs) present in exosomes derived from HTB177 cells (NCI-H460 [H460] (ATCC: HTB-177) were identified as described below.

For more detailed description please see Statello L, Maugeri M, Garre E, Nawaz M, Wahlgren J, Papadimitriou A, et al. (2018) (doi: 10.1371/journal.pone.0195969. eCollection 2018). List of the identified proteins can be found in the section 'Data collection' as well as on the journal's website (https://journals.plos.org/plosone/article?id=10.1371/journal.pone.0195969#sec025).

Identification of RNA binding proteins in exosomes and their parent cells:
To detect and isolate the RBPs in cells and exosomes, the biotinylated esRNAs, cellular miRNAs, and cellular mRNAs were attached to streptavidin-coated paramagnetic Dynabeads M-280 and were incubated with native protein extracts of exosomes in separate RNA species assays (total exosomal-protein extract + esRNA;, total exosomal-protein extract + cell-mRNA;, total exosomal-protein extract + cell-miRNA). The protein-RNA complexes were eluted from the beads. The RBPs bound to the different RNAs were then loaded onto an SDS-PAGE gel and target bands were excised, trypsinised and analyzed using LC-MS/MS. Samples without RNA were processed in parallel and were used as negative controls to identify proteins that bound non-specifically to the beads.

I människokroppen sker kommunikationen mellan celler på flera olika sätt. Exosomer är en typ av extracellulär-vesiklar (30-200 nm i diameter) som också deltar i denna process. Exosomer kan frisättas från de flesta celltyper i kroppen och förekommer naturligt i olika kroppsvätskor så som blod.

År 2007 visade vi för första gången att exosomer också transporterar RNA molekyler (både kodande och icke kodande RNA molekyler) mellan celler (Valadi H. et al. Nature Cell Biology. 2007). Resultaten beskriver en ny typ av ’cell-cell’ kommunikation med vilken olika celler skickar genetiska meddelande till varandra genom att frisätta vesiklar (exosomer) innehållande specifika RNA molekyler.

Våra nuvarande studier syftar till att (a) identifiera cellulära aktörer som deltar i trans-lokaliseringen (packning) av RNA in i exosomer under deras biosyntes, (b) ta reda på med vilken mekanism tas upp exosomer av mottagarceller/ vävnader, och (c) upptäcka en metod för att introducera exogent/ terapeutiskt RNA in i exosomer, som ska nyttjas för in vivo transport av terapeutiskt RNA till olika vävnader.

RNA-bindande proteiner (RBPs) närvarande i exosomer som härstammar från HTB177 celler (NCI-H460 [H460] (ATCC: HTB-177).

För information om identifiering se den engelska katalogposten https://snd.gu.se/en/catalogue/study/SND1142.

Mer detaljerad beskrivning finns i Statello L, Maugeri M, Garre E, Nawaz M, Wahlgren J, Papadimitriou A, et al. (2018) (doi: 10.1371/journal.pone.0195969. eCollection 2018). Lista över identifierade proteiner finns i avsnittet ’Datainsamling’ samt på tidskriftens hemsida (https://journals.plos.org/plosone/article?id=10.1371/journal.pone.0195969#sec025).
Cell till cell signalering via exosomer (transport av genetiskt material mellan celler via exosomer) - Identifiering av RNA-bindande proteiner i exosomer som kan interagera med olika typer av RNA: RBP-medierad transport av RNA till exosomer
Keywords: Cell Communication; Cellkommunikation; Extracellular Matrix; Extracellulär matrix; RNA Transport; RNA-transport; Exosomes; Exosomer; Natural Sciences; Naturvetenskap; Medical and Health Sciences; Medicin och hälsovetenskap